Crystalline Sponge Method by Three-Dimensional Electron Diffraction - Chen, Pohua; Liu, Yang; Zhang, Chaochao; Huang, Fei; Liu, Leifeng; Sun, Junliang (Frontiers in Molecular Biosciences, 2022)
The crystalline sponge method has shown to be a novel strategy for structure determination of non-crystalline, oily or trace amount of compound. The target compound was absorbed and oriented orderly in the pre-grown porous crystal for X-ray diffraction analysis. However, the diffusion in the micron-sized crystals is rather difficult. Lots of trial-and-error experiment is needed to optimize the guest-soaking process and improve data quality. Nanocrystals is better in diffusion yet it could not do the single crystal X-ray diffraction (SCXRD) analysis. 3-dimentional electron diffraction (3D-ED) is a powerful diffraction tool for small crystals. In this work, we successfully carried out the crystalline sponge method by 3D-ED technique using [(ZnI2)3-(2,4,6-tris(4-pyridyl)-1,3,5-triazine)2·x(guest)]n (1-Guest) porous complex nanocrystals. On account of the better diffuse ability of nanocrystals, the time needed for solvent-exchange and guest-soaking were shortened 50-fold faster versus the original protocol. The crystal structure of the crystalline sponge incorporated with three different guests were fully resolved using merged dataset. The structure model was identical to previously reported ones using X-ray, showing the accuracy of the 3D-ED was comparable to SCXRD. The refinement results can also give the precise occupancy of the guest molecule soaked in the porous crystal. This work not only provide a new data collection strategy for crystalline sponge method, but also demonstrates the potential of 3D-ED techniques to study host-guest interaction by solving fine structures of porous materials.